Seasonal variation in the egg morphology of the copepod Eurytemora americana and its relationship with reproductive strategy in a temperate estuary in Argentina - Berasategui, Anabela Anhi (2012)
Seasonal variation in the morphology of Eurytemora americana eggs and its relationship with reproductive strategy were studied in the Bahía Blanca Estuary. Eggs from field females were analysed morphologically by optical (OM) and electron microscopy [scanning electron microscopy (SEM)–transmission electron microscopy (TEM)] during the population pulse. Additionally, egg-carrying females were incubated simulating in situ environmental conditions to evaluate the resting egg character. Subitaneous and resting eggs were indistinguishable by OM, but showed different chorion appearance under SEM and TEM. Sinuous patterned chorion eggs, mainly produced during the period of population growth, were classed as subitaneous eggs based on their high level of  hatching success. Eggs with a sponge-like appearance, produced after the population peaked,  were classed as diapause eggs based on their inability to hatch even under favourable conditions. There were significant differences in egg size through the population pulse and diapause eggs were significantly bigger than subitaneous eggs. The observation of both morphotypes in egg-carrying females after peak population abundance confirms the existence of a transitional reproductive stage before the exclusive production of diapause eggs at the end of the pulse. Diapause egg production enables E. americana to resist adverse conditions, ensuring its survival in temperate estuaries.